PENGARUH KONSERVATISME AKUNTANSI, DEWAN KOMISARIS INDEPENDEN, PERTUMBUHAN PENJUALAN, KEPEMILIKAN SAHAM EKSEKUTIF DAN TANGGUNG JAWAB SOSIAL TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BEI 2013 – 2017 - Julia Jasmine; Emrinaldi Emrinaldi; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aimed to examine the impact of Accounting Conservatism,Independent Board of Commissioners, Sales Growth, Ownership of ExecutiveShares and Corporate Social Responsibility against tax avoidance on plantationcompanies and this research aimed to examine the effect from the variables thatcould be significantly influence or not againt Tax Avoidance. The sample used inthis research is based on criteria that have been set and totally amounted 12samples with a total of 40 data from plantation company that listed on IndonesiaStock Exchange 2013-2017. This research used purposive sampling method andtesting the hypothesis using double linear regression analysis test (Using SPSS18.0). The result from this research showed that Independent Board ofCommissioners, Sales Growth, Executive Share Ownership and Corporate SocialResponsibility partially have a significant influence against tax avoidance andAccounting Conservatism do not have a significant partial effect against taxavoidance. Results of coefficient of determination (adjusted R2) has a value 0.416.This mean that the overall effect of independent variables against Tax Avoidanceamounted 41.6%, while the remaining 58.4% is influenced by other independentvariables.Keywords : Tax Avoidance, Accounting Conservatism, Independent Board ofCommissioners, Sales Growth, Executive Share Ownership,Corporate Social Responsibility.